The Advantages and Disadvantages of Flexible Forms of Employment - Lagutina, Iryna Victorivna; Лагутіна, Ірина Вікторівна; Лагутіна, І. В.; Lagutina, Iryna V. (Одеса : Фенікс, 2026)
Flexible employment arrangements evolve over time. Time is also a critical element in that flexible employment arrangements, along with contextual requirements and available resources, can be in a state of continuous change. Today’s digitalized labour market is creating a flexible social, labour, and organizational environment that provides the opportunity to balance employees’ personal and professional lives, unlock their creative potential, and adapt to the transformations and digital advances taking place in the employment sector. Also social dialogue is essential for ensuring labour rights of employees and supporting businesses particularly by engaging in collective bargaining and other forms, methods. Social partners play a significant role thanks to their capacity in promoting decent work with the observed dynamics of the spread of flexible forms of employment.
Lagutina I. V. The Advantages and Disadvantages of Flexible Forms of Employment. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квітня 2026 р.) : у 2-х т. / за заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 1. С. 379-382. URL: https://doi.org/10.32837/11300.33193
Keywords: labour rights; employee; flexibility; employment; трудові права; працівник; гнучкість; зайнятість